Bossypants (Hachette Audio, Back Bay Books/Little, Brown, Little, Brown and Company, 2012)
From her youthful days as a vicious nerd to her tour of duty on Saturday Night Live; from her passionately halfhearted pursuit of physical beauty to her life as a mother eating things off the floor; from her one-sided college romance to her nearly fatal honeymoon, comedian Tina Fey reveals all, and proves that you're no one until someone calls you bossy.
NF Fay.

The last black unicorn (A Bestselling Comedian Memoir, ,, 2017)
The stand-up comedian and actress examines her life and career from constantly-rotated foster child to breakout star of Girls Trip.

I Even Funnier (I Funny, 2,, 2013)
"While on a mission to win the Planet's Funniest Kid Comic regional competition, New York middle schooler Jamie Grimm copes with rival comics and bullies, a buddy in trouble, and a sudden family emergency, all with a sense of humor and a loyal group of friends"--Provided by publisher.

Yes please (Dey St., an imprint of HarperCollinsPublishers, HarperAudio, 2014)
The actress best known for her work on "Parks and Recreation" and "Saturday Night Live" reveals personal stories and offers her humorous take on such topics as love, friendship, parenthood, and her relationship with Tina Fey.